Analisis Pengendalian Intern Penjualan Kredit Dalam Mengingkatkan Efektifitas Pengelolaan Piutang (Pada CV Surya Pratama Gemilang) - Kusyandi, Arini Dahlia; Pamungkas, Bambang (Jurnal Ilmiah Akuntansi Kesatuan, 2016)
Internal control of credit sales plays very important role especially in companies with most transaction done in credits. It produces procedures and policies to evaluate the effectiveness of the company’s receivables management. CV Surya Pratama Gemilang is a company running in manufacture, established to contribute products that minimize the environmental waste proble. In running its operationals, CV Surya Pratama Gemilang is in need of a good internal control in its credit sales. This is in order to produce an effective receivables management. This study aims at investigating how the internal control is applied. The research uses descriptive/case study method, by which collecting necessary data related to the existing issues to help answer the identified hypotheses. The result found that the is not running an appropriate credit sales internal control due to the existing elements of weaknesses causing the receivables to be ineffective